2022
DOI: 10.3390/plants11050611
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Cold Plasma and Electromagnetic Field as Stimulators of Natural Sweeteners Biosynthesis in Stevia rebaudiana Bertoni

Abstract: Stevioside (Stev) and rebaudioside A (RebA) are the most abundant steviol glycosides (SGs) responsible for the sweetness of Stevia rabaudiana Bertoni. As compared to Stev, RebA has a higher sweetening potency, better taste and therefore is the most preferred component of the stevia leaf extracts. The aim of this study was to determine the effect of pre-sowing seed treatment with abiotic stressors cold plasma (CP) and electromagnetic field (EMF) on the amount and ratio of RebA and Stev in the leaves of stevia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 60 publications
(98 reference statements)
1
19
3
Order By: Relevance
“…[27] Besides, the plasma-associated augmentation in the concentration of tropane alkaloids and phenols (phenylpropanoid-derivatives), as well as upregulation in the PAL activity refer to the high efficacy of plasma to act as an elicitor toward inducing secondary metabolism and defense system. Consistent with our results, the cold plasma acted as an efficient physical elicitor to enhance the biosynthesis of various secondary metabolites in diverse plant species, like phenols in Hylocereus undatus, [28] diosgenin metabolites in Trigonella foenum-graecum, [29] natural sweeteners in in Stevia rebaudiana, [18] cannabinoids in Cannabis indica, [30] phenylpropanoid derivatives in S. rabaudiana, [31] F tropane alkaloids in D. inoxia, [11] flavonoids in Echinacea purpurea, [32] and phenols in Oryza sativa. [31] Darigh et al suggested the involvement of the WRKY and ERF transcription factors in the plasma-mediated signal transduction, thereby growth performance, and metabolism can be up-regulated.…”
Section: Discussionsupporting
confidence: 86%
“…[27] Besides, the plasma-associated augmentation in the concentration of tropane alkaloids and phenols (phenylpropanoid-derivatives), as well as upregulation in the PAL activity refer to the high efficacy of plasma to act as an elicitor toward inducing secondary metabolism and defense system. Consistent with our results, the cold plasma acted as an efficient physical elicitor to enhance the biosynthesis of various secondary metabolites in diverse plant species, like phenols in Hylocereus undatus, [28] diosgenin metabolites in Trigonella foenum-graecum, [29] natural sweeteners in in Stevia rebaudiana, [18] cannabinoids in Cannabis indica, [30] phenylpropanoid derivatives in S. rabaudiana, [31] F tropane alkaloids in D. inoxia, [11] flavonoids in Echinacea purpurea, [32] and phenols in Oryza sativa. [31] Darigh et al suggested the involvement of the WRKY and ERF transcription factors in the plasma-mediated signal transduction, thereby growth performance, and metabolism can be up-regulated.…”
Section: Discussionsupporting
confidence: 86%
“…High-voltage electrical discharge plasma technology showed the potential to improve drought and salt tolerance in wheat [ 40 ]. Short-time pre-sowing treatment of stevia seeds with CAP and electro-magnetic field could enhance of biosynthesis of steviol glycosides responsible for the sweetness [ 54 ]. A positive effect of CAP on soybean germination could be achieved, and the percentage of germination increased by almost 20% compared to the untreated control [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, exposure of soybean seeds to plasma was associated with modi cation in the transcription levels of energy metabolism-related genes and several growthregulating factors (GRFs), which play vital roles in controlling plant growth and development [24]. Taking the recorded increase in tropane alkaloids into account, the application of cold plasma accelerated the accumulation of secondary metabolites in different plant species, such as, Stevia rabaudiana [17], Oryza sativa [25], cannabis [21], Datura inoxia [10], red clover [26], and Fenugreek [27].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma treatment has been investigated for its potential molecular effects on plants, particularly in terms of gene expression [14,10], epigenetic regulation [10,15], stress resistance [15], pathogen inactivation ([16], and metabolic pathways [17]. Literature data suggest that the plasma treatment can promote defense mechanisms and enhance plant growth, development, and metabolism [18].…”
Section: Introductionmentioning
confidence: 99%